Relationship between neutrophil to lymphocytes ratio, red cell distribution width, procalcitonin, neutrophil to albumin ratio, and bun to albumin ratio with mortality of severe cap patients with septic shock - Cahyani, Kadek Mien Dwi; Candrawati, Ni Wayan; Arisanti, Ni Luh Putu Eka; Suryana, Ketut; Kusumawardani, Ida Ayu Jasminarti Dwi; Artana, I. Gusti Ngurah Bagus; Rai, Ida Bagus Ngurah (International Journal of Advances in Medicine, 2024)
Background: Septic shock is one of severe community-acquired pneumonia (CAP) complication with high mortality. Various laboratory parameters had been associated with poor outcome including neutrophil-to-lymphocyte ratio (NLR), red cell distribution width (RDW), procalcitonin, neutrophil to albumin ratio (NAR), and bun to albumin ratio (BAR). This study aimed to know the relationship between inflammatory markers with mortality of severe CAP patients with septic shock. Methods: This study is an observational analytic study using a cohort retrospective design conducted in Prof. I.G.N.G. Ngoerah General Hospital over a 3 years’ period (January 2020 to July 2023). The relative risk (RR) values showed relative risk of each parameter to mortality. Results: Of total 73 subjects, mortality was found in 68.5%. Male predominance was found (65.8%). Comorbid disease was reported in 69 subjects (94.5%), most found was cardiovascular disease (63%). Majority of the subjects did not have history of prior antibiotics use (86.3%). In multivariate analysis, it was found that NLR with cutoff ≥16.5 (p value 0.044; 95% CI 1.039-14.011; RR 3.816), procalcitonin ≥1.82 (p value 0.029; 95% CI 1.148-13.560; RR 3.945), and BAR ≥8.13 (p value 0.003; 95% CI 1.961-21.912; RR 7.399) are associated with mortality. There was no relationship between RDW ≥14.65 (p value 0.159; 95% CI 0.658-12.877) and NAR ≥4.5 (p value 0.436; 95% CI 0.429-7.106) with mortality in this study. Conclusions: Mortality of severe CAP patients with septic shock in this study is high. Higher NLR, procalcitonin, and BAR values have a significant relationship with mortality of severe CAP patients with septic shock.